Regional Differences in and Influencing Factors of Animal Epidemic Risk in China - Li, Yanling; Sun, Long; Zhou, Wei; Su, Qingsong (Frontiers in Veterinary Science, 2020)
Based on data from three major pig diseases, this study calculated the animal disease epidemic index of 31 provinces and autonomous regions in mainland China. We adopted the Gini coefficient to investigate the interregional differences in animal disease epidemic risk and used the Shapley value decomposition method to illustrate the contribution of influencing factors. The results showed that the Gini coefficient remains above 0.60, indicating significant interregional differences in mainland China. Animal breeding level, ecological environment, and animal disease prevention and control contribute most to the interregional differences in animal epidemic risk. The results imply that reducing sewage discharge, increasing pig production, and changing the breeding style from free-range to large-scale farming are measures that may help improve disease prevention and control. This study has implications for providing theoretical references for preventing and controlling animal epidemics and for improving public health governance.